Fatty liver is a good indicator of subclinical atherosclerosis risk in obese children and adolescents regardless of liver enzyme elevation. (29th December 2012) - Akın, Leyla; Kurtoglu, Selim; Yikilmaz, Ali; Kendirci, Mustafa; Elmalı, Ferhan; Mazicioglu, Mümtaz
Abstract Aim To investigate the presence of association between nonalcoholic fatty liver disease (NAFLD) and subclinical atherosclerosis using carotid intima media thickness (c‐IMT) in obese children and adolescents. Additionally, we wished to investigate the relationship between fatty liver and elevated liver enzymes. Methods A total of 157 obese patients (78 boys and 79 girls, mean age: 11.3 ± 2.6 years, age range: 6–16 years) were enrolled in the study. Aminotransferase, fasting glucose and lipid levels were determined. An oral glucose tolerance test was performed. The c‐IMT was measured. Infectious and metabolic causes of elevated liver enzymes were excluded. The diagnosis of NAFLD was based on ultrasound scan. Results Obese patients with NAFLD had markedly increased carotid IMT (mean: 0.48 mm, 95% CI: 0.47–0.49) than those without NAFLD (mean: 0.45 mm 95% CI: 0.44‐0.45, p < 0.001). The presence of NAFLD significantly increased c‐IMT whether the patient had elevated liver enzyme or not (ANOVA, p < 0.001). In a multiple‐regression model, only the presence of NAFLD was associated with increased c‐IMT (β = 0.031, SE (β) = 0.008, p < 0.001). Conclusion Obese children and adolescents with NAFLD are at risk of early atherosclerotic changes. As liver function tests are not sufficient to identify patients with fatty liver, ultrasonographic evaluation of NAFLD might be considered in all obese children and adolescents.